2011
DOI: 10.1016/j.jsbmb.2011.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Oleoyl-estrone is a precursor of an estrone-derived ponderostat signal

Abstract: Oleoyl-estrone (OE) is a powerful anti-obesity compound that decreases food intake, decreases insulin resistance and circulating cholesterol. OE stimulates a severe loss of body fat by decreasing adipose tissue lipid synthesis and maintaining lipolysis. Therefore, the body economy loses lipid energy because energy expenditure is maintained. This study analyses the discrepancy between OE effects and the distribution of labelled OE in plasma. Estrone radioimmunoassay of organic solvent plasma extracts of rats tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…The list of factors potentially modifying body fat set-point is longer: estrone (Ferrer-Lorente et al, 2005; and the ponderostat signal derived from estrone; Vilà et al, 2011) dehydroepiandrosterone (Tchernof and Labrie, 2004), progesterone, aldosterone. In addition, the possibilities of regulation include retinoids (Kriegsfeld and Silver, 2004), hydroxycalciferols (Wortsman et al, 2000), hormone-transporting globulins (Barat et al, 2005; Li et al, 2010), and especially, hormone receptors (Mauvais-Jarvis, 2011).…”
Section: Schedules For Development Of the Metabolic Syndrome In Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The list of factors potentially modifying body fat set-point is longer: estrone (Ferrer-Lorente et al, 2005; and the ponderostat signal derived from estrone; Vilà et al, 2011) dehydroepiandrosterone (Tchernof and Labrie, 2004), progesterone, aldosterone. In addition, the possibilities of regulation include retinoids (Kriegsfeld and Silver, 2004), hydroxycalciferols (Wortsman et al, 2000), hormone-transporting globulins (Barat et al, 2005; Li et al, 2010), and especially, hormone receptors (Mauvais-Jarvis, 2011).…”
Section: Schedules For Development Of the Metabolic Syndrome In Adultsmentioning
confidence: 99%
“…Deranged maintenance of ponderostat settings caused by –or parallel to– altered secretion/detection of ponderostat signals, including sensitivity to peptides [leptin (Eikelis et al, 2007), adiponectin (Tomita et al, 2008)] and the postulated estrone-derived ponderostat signal (Vilà et al, 2011). …”
Section: The Roles Of Steroid Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the HPLC‐MS/MS values obtained for true OE levels in rat plasma (even after an oral load of OE) were only a tiny fraction of the results obtained using the hydrolysis‐RIA methods, and in no way justified the high levels of labelled estrone found in plasma after an oral gavage of 3 H‐or 2 H‐labelled OE. The analysis of samples with tritium or 14 C‐labelled estrone proved that the estrone nucleus label did not correspond to the elution time of OE in the HPLC‐MS/MS setting . The data unequivocally proved, then, that the active form of OE transported in the plasma does not correspond to the chemical structure of OE.…”
Section: The Circulating Oleoyl‐estrone Derivative W Structure and mentioning
confidence: 94%
“…As the secretion capacity of leptin differs within different fat depots depending on the age, gender, and circadian rhythm, the likelihood that leptin represents a true ponderostat signal is low (79, 80, 81, 82). Recent studies have demonstrated that oleoyl-estrone itself cannot be responsible for the control of body fat, but a derivate might (83). In other words, the brain is involved in the pathogenesis of metabolic syndrome, but the exact mechanisms remain obscure.…”
Section: Pathophysiology Of Metabolic Syndromementioning
confidence: 99%